2014
DOI: 10.1097/tp.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Renal Outcomes of Liver Transplant Recipients Who Had Pretransplant Kidney Biopsy

Abstract: The most LT recipients with minimal chronic changes on pre-LT kidney biopsy recovered kidney function within 1 month from LT. A small but significant percentage met criteria for kidney transplantation at 1 year because of the development of unforeseen post-LT complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…The imprecision of creatinine‐based estimates of GFR in the setting of decompensated liver disease, although well‐known, is also difficult to accurately account for in clinical practice, making pre‐LT estimates of renal dysfunction less reliable . While biopsy criteria have been suggested to quantify irreversible damage objectively, the performance of renal biopsies is infrequent in clinical practice, limited by end‐stage liver disease coagulopathy, and was associated with ~10% incidence of renal arterial embolization in a series from a tertiary referral center . Hence, the critical level of pre‐LT renal dysfunction (ie, CKD3 and listing eGFR) that best captures the presence of irreversible renal damage, that would then accurately reflect the post‐LT risk of ESRD and mortality has been a source of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imprecision of creatinine‐based estimates of GFR in the setting of decompensated liver disease, although well‐known, is also difficult to accurately account for in clinical practice, making pre‐LT estimates of renal dysfunction less reliable . While biopsy criteria have been suggested to quantify irreversible damage objectively, the performance of renal biopsies is infrequent in clinical practice, limited by end‐stage liver disease coagulopathy, and was associated with ~10% incidence of renal arterial embolization in a series from a tertiary referral center . Hence, the critical level of pre‐LT renal dysfunction (ie, CKD3 and listing eGFR) that best captures the presence of irreversible renal damage, that would then accurately reflect the post‐LT risk of ESRD and mortality has been a source of debate.…”
Section: Discussionmentioning
confidence: 99%
“…12 While biopsy criteria have been suggested to quantify irreversible damage objectively, the performance of renal biopsies is infrequent in clinical practice, limited by end-stage liver disease coagulopathy, and was associated with ~10% incidence of renal arterial embolization in a series from a tertiary referral center. 13 Hence, the critical level of pre-LT renal dysfunction (ie, CKD3…”
Section: Discussionmentioning
confidence: 99%
“…In addition, post-LT factors such as calcineurin inhibitor (CNI) use have been linked to post-LT renal dysfunction (1). Our group previously demonstrated that peri-LT events including infections and need for surgical reexploration are associated with post-LT renal dysfunction, even in patients who had normal histology on pre-LT renal biopsy (7).…”
Section: Introductionmentioning
confidence: 99%
“…The biopsy procedure has been described previously . Briefly, the international normalized ratio (INR) and platelet count were measured prior to the biopsy, and fresh frozen plasma (FFP) and/or single‐donor platelets were transfused if the INR was >1.5 or if the platelet count was <50,000/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The biopsy procedure has been described previously. (9,12) Briefly, the international normalized ratio (INR) and platelet count were measured prior to the biopsy, and fresh frozen plasma (FFP) and/or singledonor platelets were transfused if the INR was >1.5 or if the platelet count was <50,000/mL. After FFP and/or platelet transfusion(s), a repeat INR and/or platelet count was obtained, and further transfusion(s) were provided as necessary to achieve an INR ≤1.5 and a platelet count >50,000/mL.…”
Section: Renal Biopsy Proceduresmentioning
confidence: 99%